Hepatitis C Virus (HCV) Direct-Acting Antiviral Therapy in Persons With Human Immunodeficiency Virus–HCV Genotype 1 Coinfection Resulting in High Rate of Sustained Virologic Response and Variable in Normalization of Soluble Markers of Immune Activation. (14th May 2020) - Anthony, Donald D; Sulkowski, Mark S; Smeaton, Laura M; Damjanovska, Sofi; Shive, Carey L; Kowal, Corinne M; Cohen, Daniel E; Bhattacharya, Debika; Alston-Smith, Beverly L; Balagopal, Ashwin; Wyles, David L
Abstract: Background: Hepatitis C virus (HCV) direct-acting antivirals are highly effective. Less is known about changes in markers of immune activation in persons with human immunodeficiency virus (HIV) in whom a sustained virologic response (SVR) is achieved. Methods: We conducted a nonrandomized clinical trial of 12 or 24 weeks of paritaprevir-ritonavir-ombitasvir plus dasabuvir (PrOD) with or without ribavirin in persons with HCV-1/HIV coinfection suppressed with antiretroviral therapy. Plasma HCV, soluble CD14 (sCD14), interferon-inducible protein 10, soluble CD163 (sCD163), interleukin 6 (IL-6), interleukin 18, monocyte chemoattractant protein (MCP-1), autotaxin (ATX), and Mac2-binding protein (Mac2BP) were measured over 48 weeks. Results: Participants were treated with PrOD for 12 (n = 9) or 24 (n = 36) weeks; the SVR rate at 12 weeks was 93%. At baseline, cirrhosis was associated with higher ATX and MCP-1, female sex with higher ATX and IL-6, older age with higher Mac2BP, higher body mass index with higher ATX, and HIV-1 protease inhibitor use with higher sCD14 levels. In those with SVR, interferon-inducible protein 10, ATX, and Mac2BP levels declined by week 2, interleukin 18 levels declined by the end of treatment, sCD14 levels did not change, and sCD163, MCP-1, and IL-6 levels changed at a single time point. Conclusions: During HIV/HCV coinfection, plasma immune activation marker heterogeneity is in part attributable to age, sex, cirrhosis, body mass index, and/or type of antiretroviral therapy. HCV treatment with paritaprevir-ritonavir-ombitasvir plus dasabuvir is highly effective and is associated with variable rate and magnitude of decline in markers of immune activation. Clinical Trials Registration: NCT02194998. Abstract : During human immunodeficiency virus/hepatitis C virus (HCV) coinfection heterogeneity in markers of immune activation is likely in part attributable to age, sex, cirrhosis, body mass index, and/or type of antiretroviral therapy. HCV treatment with direct-acting antiviral PrOD is highly effective and associated with variable decline in immune activation markers.